PROBLEMS ENCOUNTERED WHEN TRANSLATING INDEFINITE ARTICLES IN THE UZBEK LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the linguistic and practical challenges involved in translating English indefinite articles (“a” and “an”) into the Uzbek language. English, as an article-based language, uses articles to convey specific grammatical and semantic meanings, such as indefiniteness, specificity, or countability. In contrast, Uzbek, a Turkic language, does not employ articlesat all, which creates significant difficulties for translators and language learners when trying to preserve the meaning and nuance of the original text. The absence of direct equivalents often results in ambiguity or loss of information in translation, especially in contexts where the presence of an article in English signals new or nonspecific information. The paper explores how these issues can lead to misinterpretations and shifts in meaning and provides numerous examples from real translation cases to illustrate how such problems manifest. It also highlights the role of context, word order, and other grammatical markers that may partially substitute for articles in Uzbek. Furthermore, this study investigates strategies that can be used to compensate for the lack of articles, such as the use of demonstrative pronouns, quantifiers, or restructured sentences to preserve the intended meaning.